Transfer factors peptides (Imuno TF®) modulate the lung inflammation and airway remodeling in allergic asthma - Oliveira, Carlos Rocha; Carvalho, Jessica; Olímpio, Fabiana; Vieira, Rodolfo; Aimbire, Flavio; Polonini, Hudson (Frontiers in Immunology, 2023)
Background: Asthma is a chronic disease with impacts on public health. It affects the airways causing pulmonary inflammation mediated by CD4 T cells type Th2, eosinophilia, mucus hypersecretion, and elevated IgE. The unbalance between cytokines and transcription factors is an important feature in allergic asthma. Imuno TF® is a food supplement composed of oligo- and polypeptides with roles in immune system pathways. It has been previously demonstrated that Imuno TF® positively regulated Th1 cytokines while decreasing Th2 cytokines in human lymphocytes. Objective: Thus, we investigate the Imuno TF effect in murine allergic asthma. Methods: Mice were initially sensitized on day 0 and day 7 with OVA via i.p. and challenged with OVA i.n. on days 14, 15 and 16. Treatment with Imuno TF once a day was performed via orogastric from day 17 to day 20. Mice were euthanized on day 21. Results: The Imuno TF attenuated the eosinophils infiltration, mucus and collagen secretion, IgE production, pro-inflammatory cytokines, and STAT6 in lung. Otherwise, Imuno TF increased the anti-inflammatory cytokines as well as expression of the T-bet and Foxp3. Conclusion: Finally, Imuno TF mitigated the allergic asthma-induced lung inflammation and airway remodeling by interfering on balance between the responses of Th1/Th2 as well as Treg cells, and their respective transcription factors the T-bet/STAT6 and Foxp3.